2018
DOI: 10.1177/0333102418779557
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive dural stimulation in mice: A novel preclinical model of migraine

Abstract: Background Migraine is characterized by a collection of neurological symptoms in the absence of injury or damage. However, several common preclinical migraine models require significant damage to the skull to stimulate the dura mater, the likely source of afferent signaling leading to head pain. The goal of this study was to determine whether dural stimulation can be performed in mice using an injection that does not cause injury or damage. Methods Using mice, injections of stimuli were administered to the dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 38 publications
3
87
0
Order By: Relevance
“…Similar findings in 2 outbred species suggest that these femalespecific responses to dural CGRP are not a peculiarity of mice and are not an artifact of genetic manipulation, increasing confidence that these data may translate to other species. The acute responses of both males and females to dural IL-6 show that overall noxious responses to dural stimulation occur in males (see also Burgos-Vega et al, 2019), but that female-specific responses only occur with certain stimuli. We have also shown previously that priming to dural pH 7.0 occurs in both males and females when the primed state is initiated by IL-6 (Burgos-Vega et al, 2016), demonstrating that priming following dural stimulation is not female-specific.…”
Section: Discussionmentioning
confidence: 94%
“…Similar findings in 2 outbred species suggest that these femalespecific responses to dural CGRP are not a peculiarity of mice and are not an artifact of genetic manipulation, increasing confidence that these data may translate to other species. The acute responses of both males and females to dural IL-6 show that overall noxious responses to dural stimulation occur in males (see also Burgos-Vega et al, 2019), but that female-specific responses only occur with certain stimuli. We have also shown previously that priming to dural pH 7.0 occurs in both males and females when the primed state is initiated by IL-6 (Burgos-Vega et al, 2016), demonstrating that priming following dural stimulation is not female-specific.…”
Section: Discussionmentioning
confidence: 94%
“…Vehicle‐treated Townes SS mice displayed fewer null responses and more noxious responses to periorbital mechanical stimulation than B6;129 mice (Fig C). In mice, the sensitivity of this region is assessed when studying headache/migraine pain (Burgos‐Vega et al , ), another symptom commonly reported by individuals with SCD (Vgontzas et al , ). Treatment with 30 mg/kg gabapentin had no effect on either B6;129 or Townes SS mice facial hypersensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Calibrated von Frey filaments were also used to assess facial sensitivity to punctate mechanical stimulation as previously described (Burgos‐Vega et al , ). Animals habituated to testing chambers (acrylic cups, 6·5 cm diameter × 7·0 cm height) for 2 h on each day of the 2 days prior to testing.…”
Section: Methodsmentioning
confidence: 99%
“…For periorbital testing, mice were tested as described by [9]. Briefly, each mouse was acclimated to its own polycoated paper cup (Choice 4 oz.…”
Section: Periorbital and Plantar Tactile Sensitivitymentioning
confidence: 99%